Computational Study on Urea Concentration Profiles in Hemodialysis Hollow Fiber Membranes Under Different Blood Flow Conditions - Purwanto, Belinda Kezia; Nurkhamidah, Siti; Rahmawati, Yeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Kidney failure significantly impairs physiological functions, primarily due to the accumulation of urea in the bloodstream. When renal function drops below 75%, hemodialysis becomes a crucial therapeutic intervention. This study investigates the performance of a hollow fiber dialyzer, consisting of a shell-side dialysate flow, a semi-permeable membrane, and internal capillaries for blood flow. The main objective is to develop a theoretical model describing urea mass transfer through the membrane during hemodialysis. The analysis focuses on the effect of blood flow rate on urea concentration distribution across the tube, membrane, and shell regions in both axial and radial directions. Additionally, the influence of membrane length and dialysate flow rate on urea clearance is examined. Simulation results indicate that higher blood flow rates lead to elevated urea concentrations at the tube outlet, suggesting reduced diffusion into the dialysate compartment. In contrast, increasing membrane length enhances urea clearance. Interestingly, the dialysate flow rate shows minimal impact on clearance efficiency. Under a fixed dialysate flow rate of 500 mL/min and a membrane length of 27 cm, the calculated urea clearance values were 21.95%, 17.06%, 14.31%, and 12.52% for blood flow rates of 200, 300, 400, and 500 mL/min, respectively